INTEGRASI COMPUTATIONAL THINKING UNPLUGGED DALAM PEMBELAJARAN NUMERASI DI SEKOLAH DASAR: STUDI LITERATUR - Luthfiana Luthfiana; Fathur Rokhman; Agung Tri Prasetyo; Deky Avrilianda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Research on computational thinking (CT) in primary education has continued to grow; however, studies that specifically synthesize the integration of Unplugged Computational Thinking into primary school numeracy learning remain limited. This study aims to analyze the forms of integration, potential impacts, developed CT components, and implementation challenges of Unplugged Computational Thinking in primary school numeracy learning. This study employed a Systematic Literature Review (SLR) approach involving articles published between 2017 and 2025. The literature was searched through Google Scholar, Scopus, and national journal portals using keywords related to computational thinking, unplugged activities, numeracy, mathematics, and primary school. The articles were selected based on inclusion criteria, namely discussing CT or unplugged activities in educational contexts, being relevant to mathematics or numeracy learning in primary education, being available in full text, and being published as scholarly works. Following the identification, screening, and eligibility assessment stages, 15 final articles were included in the analysis. Data were extracted based on research focus, methods, participants, implementation forms, main findings, and limitations, and were then synthesized narratively. The synthesis indicates that most studies report the positive potential of Unplugged Computational Thinking in helping students understand numeracy concepts through concrete activities, games, simulations, and contextual problem-solving. This approach also supports the development of decomposition, pattern recognition, abstraction, and algorithmic thinking. Nevertheless, its implementation is influenced by teacher readiness, activity design, and contextual suitability. These findings highlight the novelty of this review in connecting Unplugged CT with primary school numeracy and provide a basis for developing more inclusive and contextual numeracy learning. ABSTRAK Kajian tentang computational thinking (CT) dalam pendidikan dasar telah berkembang, tetapi studi yang secara khusus mensintesis integrasi Computational Thinking Unplugged dalam pembelajaran numerasi sekolah dasar masih terbatas. Penelitian ini bertujuan untuk menganalisis bentuk integrasi, potensi dampak, komponen CT yang berkembang, serta tantangan implementasi Computational Thinking Unplugged dalam pembelajaran numerasi di sekolah dasar. Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) terhadap artikel yang dipublikasikan pada rentang 2017–2025. Literatur ditelusuri melalui Google Scholar, Scopus, dan portal jurnal nasional dengan kata kunci yang berkaitan dengan computational thinking, unplugged activities, numeracy, matematika, dan sekolah dasar. Artikel diseleksi berdasarkan kriteria inklusi, yaitu membahas CT atau aktivitas unplugged dalam konteks pendidikan, relevan dengan pembelajaran matematika atau numerasi di jenjang pendidikan dasar, tersedia dalam teks lengkap, dan berasal dari publikasi ilmiah. Setelah proses identifikasi, penyaringan, dan penilaian kelayakan, diperoleh 15 artikel final untuk dianalisis. Data diekstraksi berdasarkan fokus penelitian, metode, subjek, bentuk implementasi, temuan utama, dan keterbatasan, kemudian disintesis secara naratif. Hasil sintesis menunjukkan bahwa mayoritas studi melaporkan potensi positif Computational Thinking Unplugged dalam membantu siswa memahami konsep numerasi melalui aktivitas konkret, permainan, simulasi, dan pemecahan masalah kontekstual. Pendekatan ini juga mendukung pengembangan dekomposisi, pengenalan pola, abstraksi, dan algoritma. Namun, implementasinya masih dipengaruhi oleh kesiapan guru, desain aktivitas, dan kesesuaian konteks pembelajaran. Temuan ini menegaskan kebaruan kajian pada integrasi CT Unplugged dan numerasi sekolah dasar serta memberikan dasar bagi pengembangan pembelajaran numerasi yang lebih inklusif dan kontekstual.